COMPETÊNCIAS SOCIOCOGNITIVAS NO ENSINO DE ESTUDANTES COM TRANSTORNO DO DESENVOLVIMENTO INTELECTUAL DOS ANOS FINAIS DO ENSINO FUNDAMENTAL - COSTA, Edilene Nascimento Diniz (2023)
This research investigated the teaching process of students with Intellectual Development Disorder focusing on socio-cognitive skills, with a view to building an E- book with didactic-pedagogical proposals. For this purpose, applied research was carried out with an exploratory focus, a qualitative approach, whose procedures were of the pedagogical intervention type. Thus, the research site was the Jarbas Passarinho Integrated Unit, located in the municipality of Raposa/MA. The research participants were three elementary school teachers in the final years and a pedagogical supervisor, the research instruments were semi-structured interviews and questionnaires, made available through the Google Forms platform in form format. The results showed that all teachers claimed to have knowledge about the specificities and development of students with Intellectual Developmental Disability - IDD, in addition to revealing that they use teaching methodologies aimed at developing socio-cognitive skills, two teachers also emphasized that they have difficulties in developing them, although they emphasized that they do not have specific guidelines, tools and knowledge in the area of Special Education centered on socio-cognitive skills to teaching in the common classroom of regular education. As for the use of didactic resources, the teachers stated that although they are available, they are scarce, a fact that limits the application of methodologies to the needs of students with IDD, in the common room. As the main contribution of the research, we proposed the construction of an E-book with a focus on socio-cognitive skills, aiming at the insertion of important elements to support the relationship between theory and practice. With the research it was possible to verify the need to implement public policies of inclusive education in the investigated reality, in addition to the importance of expanding the continuing education programs that highlight themes regarding socio-cognitive competences, as well as skills inherent to the development process of students with IDD.